Hak-Hak Tersangka (Miranda Rule) pada Tahap Penyidikan dalam Kitab UU Hukum Acara Pidana - Anak Agung Putu Surya Wiguna; I Made Sepud; I Nyoman Sujana (Warmadewa Press, 2020)
The protection of the rights of a criminal suspect is very important because after all the suspect is a person whose personal independence has been taken away as a result of arrest, detention, confiscation and so on. Therefore, the law is needed to guarantee the taking of rights from these suspects. The purpose of this research is to find out the arrangements for the rights of suspects (Miranda Rule) at the investigation stage in the Criminal Code Law and to discuss legal protection of the rights of suspects (Miranda Rule) at the investigation stage. This research uses a normative legal research method using a statutory approach by examining all laws related to the writing of the rights of suspects (Miranda Rule) at the investigation stage of the Criminal Procedure Code and a conceptual approach by combining expert opinions so that it becomes a researcher's argument. The results of the research show that the regulation of the rights of suspects (Miranda Rule) at the stage of investigation in the Criminal Procedure Code is suspected in Article 1 paragraph (14) of the Criminal Procedure Code for a person who due to his actions or circumstances, based on preliminary evidence, is reasonably suspected of being the perpetrator of a criminal offense, the Miranda Rule regulation applies in law. Criminal Procedure in Indonesia. Suspects. In addition, the legal protection of the suspect at the investigation stage has explicitly tried to provide protection to avoid harsh treatment of the suspect or defendant. Investigators should have followed the rules to explain the rights of suspects. Apart from that, special attention should be paid to law enforcement in Indonesia, and it is hoped that suspects must better understand their rights as suspects so that they can defend themselves.